2012
DOI: 10.5700/rausp1051
|View full text |Cite
|
Sign up to set email alerts
|

A study of governance practices in corporate foundations

Abstract: A study of governance practices in corporate foundations Sérgio Ephim MindlinEstudo das práticas de governança em fundações empresariais É crescente a realização de investimentos sociais por meio de fundações empresariais e, portanto, é importante que se aprofunde o estudo da sua governança. Governança é conceituada como conjunto de mecanismos de incentivo e controle para superar os chamados conflitos de agência, originários da separação entre propriedade e gestão das empresas, conceito também aplicado a organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
0
4
0
2
Order By: Relevance
“…Even though the authors found a relationship, this indirect way to measure IC has several failings, as it counts on opinions, not disclosure data, to identify value. This fact goes to the wrong way of what investors, analysts, and the stock exchange commission of any country desire (Copeland et al, 2010;Mindlin, 2012). Marr and Schiuma (2004) emphasize the importance of IC in creating value and of applying rigorous research methods to measure the effectiveness of each existing model.…”
Section: Ic In Tangible Intensive Firmsmentioning
confidence: 99%
“…Even though the authors found a relationship, this indirect way to measure IC has several failings, as it counts on opinions, not disclosure data, to identify value. This fact goes to the wrong way of what investors, analysts, and the stock exchange commission of any country desire (Copeland et al, 2010;Mindlin, 2012). Marr and Schiuma (2004) emphasize the importance of IC in creating value and of applying rigorous research methods to measure the effectiveness of each existing model.…”
Section: Ic In Tangible Intensive Firmsmentioning
confidence: 99%
“…As a specific and new way of CP, corporate foundations play a very important role in public welfare and charity (Westhues & Einwiller, 2006). Corporate foundations are a kind of non-profit organizations established by profitable firms and thus show highly dependence on their founder firms in terms of resources and management, leading to their lack of independence and autonomy (Mindlin, 2012). Therefore, corporate foundations may be used as substantial tools by their founder firms to pursue economic benefits (Xu et al, 2018).…”
Section: Further Analysis Based On Corporate Foundationsmentioning
confidence: 99%
“…As the trustee, the foundation is responsible for giving donated assets to beneficiaries according to the donor's wishes. As an independent nonprofit organization, "non-distribution constraint" is an important characteristic of foundations, that is, after donors donate property to the foundation, the foundation cannot distribute net income to the donors (Mindlin, 2012). Because the donor's donation to the foundation is a unilateral legal act without forming consideration, it will not form an equal power and obligation relationship with the donated property.…”
Section: Theoretical Analysis and Research Hypothesismentioning
confidence: 99%